Analysis of Extrinsic Rewards on Work Motivation in the Apron Movement Control (AMC) Unit at Adi Soemarmo Boyolali International Airport - Heni Setyowati; Andi Syaputra (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative research that aims to analyze extrinsic rewards on work motivation in the apron movement control unit at Adi Soemarmo Boyolali Airport. Extrinsic Rewards are tangible rewards that come from outside the person himself, can be financial, such as salaries, bonuses, benefits, and can be non-financial, such as promotions. Work motivation is a state or energy that drives employees who are ordered or given assignments to achieve organizational goals. (Apron Movement Control/AMC) is an airport employee who has a license or qualification to carry out law enforcement, traffic security on the apron and aircraft parking supervision. This study took 4 respondents consisting of 2 senior employees and 2 junior employees. Methods of data collection using observation (observation), interviews and documentation. Analysis of research data is descriptive. The results of this study indicate that extrinsic rewards can increase employee motivation in the AMC unit and the rewards given by the company have been implemented properly.